The episodic Trollope and An Editor's Tales - Ratcliffe, S (Indiana University Press, 2016)
This article considers how the figure of the fictional editor, and the idea of editing, illuminates ideas of selfhood, attention, and continuity in Trollope's work. Focusing on An Editor's Tales (1869–70), and The Way We Live Now (1875), I argue that the idea of the editor, and the act of editing, provided Trollope with a productive metaphor for thinking about the idea of the self in time. Trollope is drawn to a model of selfhood that bears comparison with Galen Strawson's concept of a non-narrative or “episodic” self. Engaging with readings of Trollope as “situationist” or “akrasic,” my essay offers an alternative. I highlight the most extreme, “episodic” aspects of his writing, and consider how their formal manifestations affect our readerly response.